SENAM KAKI LANSIA DENGAN LANGGAM JAWA UNTUK MENINGKATKAN KESEHATAN KAKI DAN MENURUNKAN TINGKAT STRES LANSIA - Primanda, Yanuar; Dismayanti, Nova; Rochman, Fauzi Noor; Maswaya, Elmi Safira; Afsadien, Reshananda Affan; Berliyanti, Ema Anindita; Budi, Arief Wahyu Setya (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Physiologically, eldery have decreased body functions because of aging process which influence the physical and psyschological health, including foot problem and stress. Several foot problems experienced by elderly including pain in their joints, poor foot care, and stress among elderly. Foot exercise with traditional Javanese music “langgam Jawa” has potency to manage foot problems and stress among elderly. The objective of this social service program was to increase foot health and decrease stress level among elderly by practicing foot exercise with traditional Javanese mucis “langgam Jawa”, education and practice on foot care, and cadre of elderly (health community volunteer for elderly) training of trainer as foot exercise traniner for elderly. After the implementation of the program, the results showed that the percentage of elderly who experienced tingling sensation has decreased from 71% to 25%, pain at foot joint has decreased from 54% to 38%, and pain at knee joint when walking has decreased from 54% to 29%. Foot care behaviours have improved including checking the feet from 13% to 33%, wearing footwear inside and outside the house from 22% to 47%, and using moisturizer on feet from 14% to 39%. The average score of the Self-Report Questionnaire was decreased from 4.67 to 1.75. Foot exercise with traditional Javanese music together with foot care education are beneficial to reduce the occurrence of foot problems, improve foot care behaviours, and reduce stress among elderly.